UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL 96% DAUN SAMBILOTO (Andrographis paniculata (Burm.f.) Nees TERHADAP Propionibacterium acnes - I Putu Gede Adi Purwa Hita; Putu Yudhistira Budhi Setiawan; I Gusti Septiari; I Gusti Ngurah Agung Windra Wartana Putra (MEDFARM: Jurnal Farmasi dan Kesehatan, 2022)
Background: Acnes vulgaris is a skin disease that can reduce self-confidence in adolescence and adulthood. This disease can be caused by infection with Propionbacterium acnes bacteria and treatment of this disease using antibiotics causes a lot of resistances. One alternative that can be developed to overcome this problem is the use of herbal medicines. Objective: To determine the antibacterial activity of 96% ethanol extract sambiloto leaf (Androgaphis paniculata (Burm.f.) Nees) in inhibiting the growth of Propionbacterium acnes bacteria. Method: The maceration method was used in the preparation of extracts and a qualitative test of active compounds was carried out. The antibacterial activity test was carried out using the disc diffusion method. Results: Qualitatively identified in the extract contains several active compounds like alkaloids, flavonoids, tannins, triterpenoids and saponins. 96% ethanol extract of sambiloto leaf with concentrations of 25, 50, 75, and 100% w/v had antibacterial activity against Propionibacterium acnes, indicated by the diameter of the inhibition zone at each concentration. Conclusion: 96% ethanol extract of sambiloto leaf (Andrographis panuculata (Burm.f.) Nees) has antibacterial activity against the growth of Propionibacterium acnes bacteria where the category of strong antibacterial activity was found in samples with concentrations of 75 and 100% w/v with the diameter of the inhibition zone formed respectively 11.26±0.44 mm and 16.52 ± 1.33 mm. Keywords: Andrographis paniculata (Bum.f.) Nees, antibacterial, disc diffusion, 96% ethanol extract, Propionibacterium acnes